THE REPRESENTATION OF FOREGROUND AND BACKGROUND IN FRENCH, ENGLISH, AND GERMAN TRANSLATIONS OF JORGE AMADO´S NOVEL GABRIELA (Revista de Letras, 2016)
THE REPRESENTATION OF FOREGROUND AND BACKGROUND IN FRENCH, ENGLISH, AND GERMAN TRANSLATIONS OF JORGE AMADO´S NOVEL GABRIELA